Radial versus raster spectral-domain optical coherence tomography scan patterns for detection of macular fluid in neovascular age-related macular degeneration. Issue 4 (10th August 2015) - Adam, Murtaza K; Rayess, Nadim; Rahimy, Ehsan; Maguire, Joseph I; Hsu, Jason
Abstract : Background/aims: To compare the 12-line radial to the 25-line raster spectral-domain optical coherence tomography (SD-OCT) acquisition patterns at detecting intraretinal or subretinal fluid in eyes with neovascular age-related macular degeneration (AMD). Methods: Retrospective cross-sectional analysis of 200 eyes with neovascular AMD. Sequential 12-line radial and 25-line raster scans were evaluated for the presence of intraretinal/subretinal fluid. Results: A total of 394 SD-OCT scans were interpreted (1.97 scans per eye). The 12-line radial detected intraretinal/subretinal fluid in all but 7 of 394 scans (1.7%; 95% CI 0.7% to 3.6%), resulting in a sensitivity of 98.3%. The 25-line raster detected intraretinal/subretinal fluid in all but 10 of 394 scans (2.5%; 95% CI 1.2% to 4.6%), resulting in a sensitivity of 97.5%. This small difference in fluid detection between the two acquisition patterns for neovascular AMD was not found to be statistically significant (p=0.6276). Conclusions: The 12-line radial scan is statistically comparable with the 25-line raster scan in detecting the presence of intraretinal/subretinal fluid in neovascular AMD. The 12-line radial SD-OCT pattern alone may be adequate to guide day-to-day clinical decisions in a more time-efficient manner.